2021
DOI: 10.3389/fpsyg.2020.604340
|View full text |Cite
|
Sign up to set email alerts
|

The Four Deadly Sins of Implicit Attitude Research

Abstract: In this article, we describe four theoretical and methodological problems that have impeded implicit attitude research and the popular understanding of its findings. The problems all revolve around assumptions made about the relationships among measures (indirect vs. versus direct), constructs (implicit vs. explicit attitudes), cognitive processes (e.g., associative vs. propositional), and features of processing (automatic vs. controlled). These assumptions have confused our understandings of exactly what we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Standard indirect measures that aim to assess associations (e.g., Affective Priming, Fazio et al, 1995 ; and the IAT, Greenwald et al, 1998 ), have recently been criticized for their lack of internal and predictive validity (e.g., Meissner et al, 2019 ; Corneille and Hütter, 2020 ; Meissner and Rothermund, in press ; Rothermund et al, 2020 ; Sherman and Klein, 2021 ). In addition to that, researchers have called attention to a further limitation of the most established standard indirect measures.…”
Section: Introductionmentioning
confidence: 99%
“…Standard indirect measures that aim to assess associations (e.g., Affective Priming, Fazio et al, 1995 ; and the IAT, Greenwald et al, 1998 ), have recently been criticized for their lack of internal and predictive validity (e.g., Meissner et al, 2019 ; Corneille and Hütter, 2020 ; Meissner and Rothermund, in press ; Rothermund et al, 2020 ; Sherman and Klein, 2021 ). In addition to that, researchers have called attention to a further limitation of the most established standard indirect measures.…”
Section: Introductionmentioning
confidence: 99%
“…In the survey we asked participants to complete a lengthy questionnaire about their psychological and demographic information. Some studies (Meissner et al, 2019;Sherman and Klein, 2021) have argued that self-reported attitudes and values are often in conflict with people's actual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In the survey we asked participants to complete a lengthy questionnaire about their psychological and demographic information. Some studies (Meissner et al , 2019; Sherman and Klein, 2021) have argued that self-reported attitudes and values are often in conflict with people’s actual behaviour. Stephens-Davidowitz and Pinker (2017) suggested researchers beware of the social desirability bias - as people wish to look good (even though most surveys are anonymous) survey participants tend to inaccurately report behaviours and thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the low predictive validity of implicit measures of age stereotypes is that these measures typically aim at assessing simple associations between the category “old” and evaluative attributes. These measures of associations, however, are notoriously unreliable and ambiguous with regard to their interpretation ( Meissner et al, 2019 ; Rothermund et al, 2020 ; Sherman and Klein, 2021 ). On the one hand, associations do not have a clear meaning ( cf.…”
Section: Introductionmentioning
confidence: 99%